Corporate Governance and Human Resource Management in Nigeria’s Oil and Gas Industry - Onovwiona, Solomon; Okiti, Sweet Eno (Universitas Kuningan, 2025)
This study examines the impact of corporate governance practices on human resource management (HRM) within Nigeria’s oil and gas industry, focusing on three key aspects: employee commitment, employment contracts, and disciplinary and grievance structures. Using a sample size of 400 retrieved questionnaires from a distributed 480, the study employed statistical analyses to test three hypotheses. The findings reveal a significant positive relationship between corporate governance practices and HRM outcomes. Firstly, strong corporate governance practices were found to foster higher employee commitment, driven by transparent, ethical, and accountable leadership. This commitment enhances organizational productivity and reduces employee turnover. Secondly, corporate governance was shown to play a crucial role in the formulation of fair, transparent, and legally compliant employment contracts, which are essential for maintaining healthy labor relations in the highly regulated oil and gas sector. Thirdly, the study highlights that robust governance structures improve disciplinary and grievance procedures, ensuring fairness, reducing conflicts, and promoting organizational harmony. The study concludes that corporate governance is a critical driver of effective HRM practices in Nigeria’s oil and gas industry. By promoting accountability, transparency, and ethical leadership, organizations can enhance employee trust, motivation, and overall workplace environment. Recommendations include strengthening corporate governance frameworks through ethical leadership training, enhancing employee engagement, ensuring compliance in employment contracts, and implementing fair disciplinary and grievance structures. The study also emphasizes the need for further research to explore the evolving relationship between corporate governance and HRM practices, especially in industries facing unique operational and environmental challenges.